«Նուէր» եւ «պաշտել» բառերի մասին - Սիլվա Պապիկյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В армянском языке много заимствований из иранских языков, большая часть которых относится к среднеперсидскому периоду с IV до н.э. по X н.э. Более 1400 заимствований - религиозные слова составляют около 4,3 процентов /60 слов - 18 из которых относятся к древней религии Ирана- зороастризму/. In old period Armenian adopted most borrowings from Iranian languages, and a large number of those are adopted in Middle Iranian Period (from the 4-3rd cc. B.C to the 10th c., and especially from the 1st c. B.C to the 1st c.). Approximately 4.3 percent (60 words) of 1400 Iranian borrowings refer to religion, and 18 of them refer to Old Iranian religion, Zoroastrianism.
Keywords: Language and Literature